The twelve days of Dash & Lily - Cohn, Rachel; Levithan, David (New York Alfred A. Knopf, 2016)
Dash and Lily have had a tough year since readers first watched the couple fall in love. Lily's beloved grandfather suffered a heart attack, and his difficult road to recovery has taken a major toll on her typically sunny disposition. With only twelve days left until Christmas--Lily's favorite time of the year--Dash, Lily's brother Langston, and their closest friends take Manhattan by storm to help Lily recapture the holiday magic of New York City in December
12-17 years
1
Keywords: Families -- Juvenile fiction; Families; Holidays -- Juvenile fiction; Holidays; YOUNG ADULT FICTION / Holidays & Celebrations; YOUNG ADULT FICTION / Romance; YOUNG ADULT FICTION / Social Themes / Emotions & Feelings; Christmas -- Fiction; Families -- Fiction; Holidays -- Fiction; Families -- fiction; Holidays -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (State) -- New York; New York (N.Y.) -- Fiction; New York (N.Y) -- Fiction; Christmas stories; Christmas stories; Fiction; Juvenile works; Love stories; Romance fiction; Romance fiction